2020
DOI: 10.3390/su12187768
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Lockdowns and Changes in Body Weight among Polish Women. A Cross-Sectional Online Survey PLifeCOVID-19 Study

Abstract: There is limited information on the relationships between restrictions linked to COVID-19 and changes in body weight. The aim of the study was to identify the body weight changes and their determinants in the nutritional and socio-demographic context during the COVID-19 pandemic in Polish women. During lockdown in Poland, 34% of women gained weight, while 18% of women reduced weight. As many as 44% of women with obesity before the pandemic increased their body weight, and 74% of women that were underweight red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 61 publications
6
71
0
3
Order By: Relevance
“…Regarding dietary interventions, a healthy diet abundant in vegetables, fruits, and whole grains, and concurrently restricted in salt, fat, and sugar is recommended during the COVID-19 pandemic [ 10 ]. Nevertheless, previous results showed that during the pandemic, many people worsened their diet or/and gained weight [ 24 , 25 , 59 , 60 , 61 ]. Unfortunately, knowledge about COVID-19 prevention is not fully satisfactory [ 31 , 52 , 62 ] and often derives from social-media or media [ 52 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding dietary interventions, a healthy diet abundant in vegetables, fruits, and whole grains, and concurrently restricted in salt, fat, and sugar is recommended during the COVID-19 pandemic [ 10 ]. Nevertheless, previous results showed that during the pandemic, many people worsened their diet or/and gained weight [ 24 , 25 , 59 , 60 , 61 ]. Unfortunately, knowledge about COVID-19 prevention is not fully satisfactory [ 31 , 52 , 62 ] and often derives from social-media or media [ 52 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shortly, in the present study, we searched topics related to coronavirus, immune system, dietary supplements, nutrients, bioactive compounds, and foods related to dietary supplements and immune system. We chose those topics based on literature searches [ 11 , 14 , 16 , 17 , 22 , 23 ] and results obtained within the PLifeCOVID-19 Online Study which we conducted in April–May 2020 [ 24 , 25 ]. We searched those topics separately (non-adjusted data), as well as each topic in comparison to the topic “lutein” (adjusted data) which allowed to compare the popularity of all searched topics.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded 10 studies based on a quality assessment of the results, and 27 studies were excluded based on reasons presented in the PRISMA flow diagram (Figure 1). The range of observations covered dietary choices (14,(21)(22)(23)(24)(25)(26)(33)(34)(35)(36)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) , lifestyle changes in children (24,36,(48)(49)(50)(51) , physical activity levels (33)(34)(35)37,38,(38)(39)(40)(41)43,46,47,49,52,53,(53)(54)(55)(56)(57)(58)(59)(60) , psychosocial factors (22,23,<...>…”
Section: Categorization Of Determinantsmentioning
confidence: 99%
“…The number of participants in the included studies ranged from 41 to 381,564. All studies included both male and female participants except one study (37) . The duration of confinement for the selected studies for this systematic review ranged between 1 and 24 weeks.…”
Section: Demographic Determinants (Study and Sample Characteristics)mentioning
confidence: 99%
See 1 more Smart Citation